The employment contract with externalised costs: the avatars of Marxian exploitation. Issue 5 (3rd September 2018) - Dos Santos Ferreira, Rodolphe; Ege, Ragip
Abstract: The paper pursues two aims. The first is to argue that the foundation of Marx's theory of capitalist exploitation is to be found, not in the labour theory of value, but rather in the contract of employment, the legal frame of the capital-labour relation. The second is to suggest that the partial externalisation of the reproduction cost of labour power has been an important source of relative surplus value, along with the productivity increase, emphasised by Marx, in the industries supplying wage goods.